2000
DOI: 10.1353/at.2000.0011
|View full text |Cite
|
Sign up to set email alerts
|

Who Owns the Oil?: The Politics of Ethnicity in the Niger Delta of Nigeria

Abstract: This article evaluates conflicting ownership claims to crude-petroleum resources by the Nigerian State and by ethnic minorities of the Niger Delta. It details the colonial origin of the state's control of oil resources and the political context of the conflict. Using theoretical principles drawn from classical and modern liberals, the article considers the grounds on which each side makes its claims and rejects the sovereignty argument that Nigeria belongs to its entire people and so do the resources within it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…There is a vast, growing and valuable literature on the Ogoni more specifically and the Niger Delta more generally which touches on many themes closely related to the focus of this study. Numerous studies have assessed the Ogoni or Niger Delta self-determination claims (Ejobowah 2000, Osaghae 1995, Senewo 2015 while Frynas (2001) convincingly highlights some of the corporate and state responses to the protests we emphasize in this study. A number of studies have highlighted the corporate role in violence and human rights violations against the oil-producing communities (Manby 1999, Pegg 1999 Ukiwo's (2007) work on how the turn toward militancy is specifically connected to a consistent failure to meet peaceful demands is particularly relevant for some of the arguments advanced in this study.…”
Section: Introductionmentioning
confidence: 56%
“…There is a vast, growing and valuable literature on the Ogoni more specifically and the Niger Delta more generally which touches on many themes closely related to the focus of this study. Numerous studies have assessed the Ogoni or Niger Delta self-determination claims (Ejobowah 2000, Osaghae 1995, Senewo 2015 while Frynas (2001) convincingly highlights some of the corporate and state responses to the protests we emphasize in this study. A number of studies have highlighted the corporate role in violence and human rights violations against the oil-producing communities (Manby 1999, Pegg 1999 Ukiwo's (2007) work on how the turn toward militancy is specifically connected to a consistent failure to meet peaceful demands is particularly relevant for some of the arguments advanced in this study.…”
Section: Introductionmentioning
confidence: 56%
“…As a push back to the 'bads' they are left with, these coastal communities that depend on their ecosystem for survival but which can no longer sustain them take to 'illegal' extraction and refining of oil (Ikelegbe 2005;Onyena and Sam 2020). In this work, we adopt the use of the term 'artisanal refining' in lieu of 'illegal refining' because of the debates and conflicts surrounding the extraction of this resource found on their land for survival, whereby it is deemed rightfully legitimate in some quarters and illegal in others (Amah 2020;Ebeku 2002;Ejobowah 2000;Ikelegbe 2005; Niworu 2017; Ntor 2020; Okwelum 2021). There is the view that artisanal refiners are left with no options after the destruction of farming and fishing activities by oil exploration activities (Umukoro 2018).…”
Section: Environmental Injustice and The Wicked Problem Of Air Pollut...mentioning
confidence: 99%
“…Also, the locals who lose their farmland to oil spills are mostly not compensated. (Ejobowah, 2000;Frynas, 2000;Manby, 1999;Obi, 2006;UNDP, 2006;Welch, 1995). Accordingly, the United Nations Development Programme (UNDP), in a blunt description of the level of underdevelopment in the Niger Delta region, carefully observed that the expectations of the people are falling despite the increase of oil prices.…”
Section: The Niger Delta Region and Underdevelopmentmentioning
confidence: 99%